Community Education on the Presence of Paracetamol and Mefenamic Acid in Traditional Herbal Remedies for Muscle and Joint Pain Circulating in Lubuk Pakam - Jhon Patar Sinurat; Reh Malem Br Karo; Yohana Silvia Uli Manalu; Shofian Syarifuddin; Regina Elianda Tampubolon (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Traditional herbal medicine remains widely consumed by Indonesian communities to maintain health and alleviate various health complaints, including musculoskeletal pain. However, the high demand for herbal remedies for aches and pains is often accompanied by the circulation of products adulterated with medicinal chemical substances, such as paracetamol and mefenamic acid, which are prohibited in traditional herbal medicines. This community service program aimed to improve public knowledge and awareness regarding the presence of medicinal chemical substances in herbal remedies for musculoskeletal pain circulating within the community. The program was implemented using an educative-participatory approach through interactive lectures, group discussions, simple case studies, and question-and-answer sessions. A total of 40 participants were selected through purposive sampling and attended all stages of the program. Evaluation was conducted using pre-test and post-test questionnaires, participation observation sheets, and participant satisfaction surveys. The results demonstrated a substantial improvement in participants’ knowledge, with the mean score increasing from 57.63 in the pre-test to 86.25 in the post-test, representing an increase of 28.62 points. The proportion of participants categorized as having good knowledge increased from 15.0% to 85.0%, while those in the poor knowledge category decreased from 45.0% to 2.5%. Participant engagement was also high, with 82.5% categorized as active or highly active throughout the program. Satisfaction assessment revealed that more than 95% of participants were satisfied or very satisfied with the overall implementation of the activity. These findings indicate that the educational intervention was effective in enhancing public understanding of the risks associated with medicinal chemical substances in traditional herbal products and encouraging the selection of safe herbal medicines for consumption.